New light on the endemic South American pachyrukhine Paedotherium Burmeister, 1888 (Notoungulata, Hegetotheriidae): Taphonomic and paleohistological analysis - Tomassini, Rodrigo Leandro (2017)
Paedotherium is a small notoungulate endemic of South America, very abundant in the Neogene assemblages of the Argentine Pampas. Numerous specimens of this taxon were recovered in the Arroyo Chasicó Formation (Late Miocene), following a strict control of their stratigraphic provenance. In this context, a detail taphonomic and paleohistological study were performed, and the results obtained were compared with the information of other Neogene assemblages of Argentina previously studied, in order to interpret the relevance of this taxon in the biocoenosis and taphocoenosis corresponding to this lapse. Before burial, specimens were affected by diverse biostratinomic processes, according to the particular characteristics of each preservational context. After burial, the specimens were modified by the same fossil-diagenetic processes. Similar patterns of preservation were identified in specimens of Paedotherium recovered in other Neogene fluvial deposits of the Argentine Pampas. Based on the bone microstructure, it was possible to differentiate juvenile and adult individuals belonging to different Neogene species of Paedotherium. The mandibles of this taxon maintained the same ontogenetic growth strategy throughout the Late Cenozoic. This work provides novel data on paleoecological and paleobiological features of this taxon.